2017
DOI: 10.1186/s13098-017-0221-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of menopause and diabetes on atherogenic lipid profile: is it worth to analyse lipoprotein subfractions to assess cardiovascular risk in women?

Abstract: Cardiovascular disease is the leading cause of death in women at advanced age, who are affected a decade later compared to men. Cardiovascular risk factors in women are not properly investigated nor treated and events are frequently lethal. Both menopause and type 2 diabetes substantially increase cardiovascular risk in the female sex, promoting modifications on lipid metabolism and circulating lipoproteins. Lipoprotein subfractions suffer a shift after menopause towards a more atherogenic lipid profile, consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 177 publications
(169 reference statements)
3
34
0
5
Order By: Relevance
“…The serum TG and HDL-C levels improved in both sexes with increasing BWR and in the group with a %BWC < -3% to -5% only in men. In women, serum lipid levels change with age; TG levels rapidly increase after the age of about 50 years in women due to menopause 22 and this may complicate the serum lipid change by BWR in women.…”
Section: Weight Reduction and Metabolic Parametersmentioning
confidence: 99%
“…The serum TG and HDL-C levels improved in both sexes with increasing BWR and in the group with a %BWC < -3% to -5% only in men. In women, serum lipid levels change with age; TG levels rapidly increase after the age of about 50 years in women due to menopause 22 and this may complicate the serum lipid change by BWR in women.…”
Section: Weight Reduction and Metabolic Parametersmentioning
confidence: 99%
“…The direct impact of insulin resistance on lipid metabolism in type 2 diabetes DMT2 is quite well-known, while in DM type 1 the mechanisms related to insulin deficiency and dyslipidaemia remain poorly understood and controversial. According to studies, diabetes generally promotes not only quantitative changes in the amount of circulating lipids – particularly an increase in triglycerides and LDL as well as a reduction in HDL but also qualitative and kinetic in nature [ 59 61 ]. Decreased plasma concentration, triacylglycerol enrichment, reduced phospholipids, ApoE and ApoM, glycation and increased HDL catabolism are the main changes occurring in diabetes [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…For specific characteristics, ageing or postmenopause mechanistically predisposes individuals to decreased NO bioavailability, increased oxidative stress, inflammation, and atherogenic lipid profiles, contributing to an increased risk of developing CVD [ 42 , 43 ]. Increasing evidence has also shown that the adverse events of NO bioavailability, oxidative stress, and inflammation similarly exist in diabetes mellitus, hypercholesterolaemia, hypertension, and chronic kidney disease [ 44 47 ].…”
Section: Discussionmentioning
confidence: 99%